THE ROLE OF THE INTERNATIONAL MONETARY FUND IN THE 1998 REFORM CONFLICT IN INDONESIA - Rizqa Aliefiarahma (Jurnal Ekonomi, 2023)
The conflict of Economic Crisis that occurred in Indonesia during the Soeharto era in 1997 was a situation due to the influence of economic conditions in neighboring countries, which caused the rupiah exchange rate to be depressed. As a result of this situation, Indonesia decided to request economic assistance from the International Monetary Fund, where the IMF provided a number of loans under conditions agreed by Indonesia. This article was written with the aim of discussing what role did the IMF gave to the Reformation that took place in 1998. This research will be using qualitative methods carried out by analysis of case studies and review of related documents and archives. The results that can be found from this article are in fact, the assistance provided by the IMF only provides temporary solution and brings further problems from the economic crisis. The agreement between the Indonesian government and the IMF actually harmed the course of the Indonesian economy and worsened the situation at that time.